AFTER FOUR YEARS - Johana Murti; Ribut Basuki (Kata Kita: Journal of Language, Literature, and Teaching, 2016)
In this creative work, I would like to highlight marriage problems in Indonesia that is faced by people from two different generation through a theatre play. In my script, there is a mother and a daughter as representatives of two different generation. The marriage problem is faced by the daughter, and the mother tries to give solutions based on her own knowledge and values. This creative work focuses on the difference of how the mother and the daughter respond to the marriage problem. I would also point out about how generational gap problem affects the way the mother and the daughter respond to the marriage problems. To put this issue into a form of entertainment, I decided to make a drama play which type of genre is almost similar to our real life.